Sensitivity of eye-movement measures to in-vehicle task difficulty - Victor, Trent W.; Harbluk, Joanne L.; Engström, Johan A. (Transportation research. Part F, Traffic psychology and behaviour, 2005)
Eye-movement measures were found to be highly sensitive to the demands of visual and auditory in-vehicle tasks as well as driving task demands. Two newer measures, Percent road centre and Standard deviation of gaze, were found to be more sensitive, more robust, more reliable, and easier to calculate than established glance-based measures. The eye-movement measures were collected by two partners within the EU project HASTE to determine their sensitivity to increasingly demanding in-vehicle tasks by means of artificial, or surrogate, In-vehicle Information Systems (S-IVIS). Data from 119 subjects were collected from four routes: a motorway in real traffic with an instrumented vehicle, a motorway in a fixed base simulator, and from rural roads in two different fixed base simulators. As the visual task became more difficult, drivers looked less at the road centre area ahead, and looked at the display more often, for longer periods, and for more varied durations. The auditory task led to an increasing gaze concentration to road centre. Gaze concentration to the road centre area was also found as driving task complexity increased, as shown in differences between rural curved- and straight sections, between rural and motorway road types, and between simulator and field motorways.